Characterisation of galactinol synthase II (XvGolSII) from the resurrection plant Xerophyta viscosa (Baker) - Neumann, Alexis Joy (Department of Molecular and Cell Biology, 2014)
The monocotyledonous Xerophyta viscosa belongs to a unique group of angiosperms known as resurrection plants. These plants possess a number of unique characteristics which allow them to survive and cope for extended periods with extreme abiotic stresses such as dehydration and cold stress. It is therefore of great interest to understand and elucidate the various molecular mechanisms which are specifically regulated in response to abiotic stress by identifying genes and proteins which may contribute to abiotic stress tolerance. These genes could potentially be utilized in the development of crops with improved tolerance to abiotic stresses. The aim of this study was to preliminarily characterize XvGolSII, a galactinol synthase, which had been isolated from a X. viscosa cold stress cDNA library. In this study, the XvGolSII cDNA was sequenced and both the nucleic and amino acid sequence analysed through in silico analysis. The XvGolSII cDNA sequence was shown to be 1434 bp in length, with an open reading frame (ORF) of 1018 bp. This ORF encodes a 339 amino acid protein with a molecular weight of 38.7 kDa, containing a characteristic hydrophobic carboxyterminal pentapeptide, APSAA. Recombinant XvGolSII protein was successfully expressed in E. coli BL21 cells using the pET29b expression vector. The recombinant XvGolSII protein showed in vitro galactinol synthase activity via an activity assay using HPAEC-PAD, where it produced galactinol from the substrates myo-inositol and UDPgalactose. Subcellular localisation examination, using an XvGolSII-YFP fusion protein, indicated localisation to the cell membrane of onion epidermal cells. Quantitative real time PCR analysis showed XvGolSII to be significantly down-regulated during dehydration stress while mildly up-regulated during the early stages of cold stress, though the latter increase was not significant. Western blot analyses did not detect XvGolSII in total protein extracted from X. viscosa leaf tissue during dehydration and rehydration treatments, using polyclonal antibodies generated from the XvGolSII recombinant protein. This study successfully characterized XvGolSII at the molecular level and provides a basis for further investigation of the role of XvGolSII in abiotic stress tolerance.